A comparison of reactivating efficacy of newly developed oximes (K074, K075) and currently available oximes (obidoxime, HI-6) in cyclosarin-and tabun-poisoned rats - Kassa, Jiri; Jun, Daniel; Kuca, Kamil (Journal of enzyme inhibition and medicinal chemistry, 2007)
The potency of newly developed oximes (K074, K075) and commonly used oximes (obidoxime, HI-6) to reactivate nerve agent-inhibited acetylcholinesterase was evaluated in rats poisoned with tabun or cyclosarin at a lethal dose corresponding to the LD50 value. In vivo determined percentage of reactivation of tabun-inhibited blood and brain acetylcholinesterase showed that obidoxime is the most efficacious reactivator of tabun-inhibited acetylcholinesterase among studied oximes in the peripheral compartment (blood) although the differences between obidoxime and newly developed oximes were not significant. On the other hand, one of the newly developed oximes (K074) seems to be a significantly more efficacious reactivator of tabun-inhibited acetylcholinesterase in the central compartment (brain) than the other studied oximes. In addition, the oxime HI-6 is unable to sufficiently reactivate tabun-inhibited acetylcholinesterase in rats. In vivo determined percentage of reactivation of cyclosarin-inhibited blood and brain acetylcholinesterase in poisoned rats showed that HI-6 is the most efficacious reactivator of cyclosarin-inhibited acetylcholinesterase among the studied oximes in the peripheral (blood) as well as central (brain) compartment although the differences between the oxime HI-6 and other tested oximes in the brain were not significant. Due to their reactivating effects, both newly developed K-oximes can be considered to be promising oximes for the antidotal treatment of acute tabun poisoning while the oximes HI-6 is still the most promising oxime for the treatment of acute cyclosarin poisonings due to its high potency in reactivating cyclosarin-inhibited acetylcholinesterase in the peripheral as well as central compartment.
Keywords: Animals; butany; antidota; Rats, Wistar; Organophosphorus Compounds; oximy; otrava organofosfáty; Pyridinium Compounds; Structure-Activity Relationship; pyridinové sloučeniny; Antidotes; organofosforové sloučeniny; Drug Evaluation, Preclinical; mozek; Organophosphates; Butanes; preklinické hodnocení léčiv; Oximes; Male; Obidoxime Chloride; Brain; organofosfáty; reaktivátory cholinesterasy; obidoxim chlorid; krysa rodu Rattus; vztahy mezi strukturou a aktivitou; zvířata; mužské pohlaví; Organophosphate Poisoning; Rats; Cholinesterase Reactivators; potkani Wistar